2021
DOI: 10.1371/journal.pone.0257393
|View full text |Cite
|
Sign up to set email alerts
|

Word learning in the field: Adapting a laboratory-based task for testing in remote Papua New Guinea

Abstract: Adapting laboratory psycholinguistic methods to fieldwork contexts can be fraught with difficulties. However, successful implementation of such methods in the field enhances our ability to learn the true extent and limitations of human behavior. This paper reports two attempts to run word learning experiments with the small community of Nungon speakers in Towet village in the Saruwaged Mountains, Papua New Guinea. A first attempt involved running a cross-situational task in which word-object pairings were pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…First, participants may have a lack of familiarity with the notion of someone presenting stimuli multiple times and asking for a response or an opinion. This was encountered previously by Mulak et al, [46], who conducted a word learning study in the same area, and interpreted their null result as possibly reflecting a lack of familiarity with the task. Important to note is that Mulak et al, [46] concluded this based on a predominance of patterned responses, a type of response we already excluded from consideration in this study.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…First, participants may have a lack of familiarity with the notion of someone presenting stimuli multiple times and asking for a response or an opinion. This was encountered previously by Mulak et al, [46], who conducted a word learning study in the same area, and interpreted their null result as possibly reflecting a lack of familiarity with the task. Important to note is that Mulak et al, [46] concluded this based on a predominance of patterned responses, a type of response we already excluded from consideration in this study.…”
Section: Discussionmentioning
confidence: 60%
“…This was encountered previously by Mulak et al, [46], who conducted a word learning study in the same area, and interpreted their null result as possibly reflecting a lack of familiarity with the task. Important to note is that Mulak et al, [46] concluded this based on a predominance of patterned responses, a type of response we already excluded from consideration in this study. Many research experiments are designed with a particular cultural influence and these designs may be interpreted differently in another culture [46,63].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The experiment did not work as expected and the author admits that one reason might be that the speakers who recorded the utterances were well-respected senior members of the community and that it may have been culturally and socially inappropriate for the participants in the study to challenge what the elders said by qualifying their statements as 'false.' Another interesting example of both a failed and a successful experiment is related in Mulak et al (2021). A team of researchers, including researchers who were familiar with the community, conducted a word learning experiment with 34 Nungon speakers from Papua New Guinea.…”
Section: Challengesmentioning
confidence: 99%